Foraging and scavenging in nautilus (Nautilus sp.) L. (Cl. Cephalopoda). Issue 5 (17th November 2021) - Barord, Gregory J.; Beydoun, Mohammed; Bruce, Spencer; Li, Virginia; Ward, Peter D.; Basil, Jennifer
ABSTRACT: Species of extant nautiluses (in Nautilus and Allonautilus ) have been anecdotally described as opportunistic scavengers. Here, we examine foraging and scavenging behaviors of Nautilus in field and laboratory settings. Given that nautiluses are nektobenthic, solitary animals living in resource-limited habitats, we predict that odor is the predominant cue used to locate prey. Here, we show that nautiluses display a stereotyped set of search postures in the wild. In field and laboratory trials, nautiluses displayed the same stereotyped foraging postures, suggesting it is a natural and functional reflex in nautilus, and can be replicated under controlled conditions. A series of foraging behaviors induced by olfaction is a highly desirable trait to scavenge for food in the deep-sea. Considering the recent conservation initiatives and regulations now in place to protect declining nautilus populations, understanding and describing feeding behaviors and the ecology of nautiluses are a critical component to support conservation efforts.